(untitled) (Revista científica Olimpia, 2021)
A pedagogic strategy to promote the participation and Primary implication of all of the pupils in the sports activities from the inclusive practices in the educational level from the work in net, with the implication of all of the educational agents in the attention to the diversity proposes the article. The investigation is a part of a study on the mentioned subject matter that evidences psychological, pedagogic and sociological congruent basics with the inclusive practices.